REALITIES AND PROSPECTS OF UKRAINE BANKING SYSTEM - Oksana Agres; Ruslana Sodoma; Oksana Sadura (Фінансово-кредитна діяльність: проблеми теорії та практики, 2017)
The article deals with the necessity of effective banking system functioning for successful economic development. The Ukrainian banking sector under the conditions of unstable financial, economic and political situation is analyzed. The basic problems, which the banks faced by in the course of their business, such as a low credit and investment ratings, total distrust of financial institutions, rapid devaluation of the hryvnia, are grounded. It is represented the dynamics of the changes in the number of banking institutions, dynamics of indices of their activities, changes in the discount rate for lending of the real economy sector by commercial banks. It is found that reducing the number of banks would mean increasing their reliability. The reasons of commercial banks liquidation are determined. The necessity of nationalization of JSC "Privatbank" is grounded. On the base of the analysis the recommendations of stabilization the banking system, the main of which are the start of lending and effective risk management are offered.